Measuring the Effectiveness of the Education Sector in Achieving Sustainable Development in Libya (1962–2022) - SHohoob, Ali M.; Doub, Hajer A. (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
This study highlights the relationship between the education sector in Libya and sustainable development during the period 1962-2022, where education is considered a fundamental basis for developing human capital and achieving sustainable development goals. The primary objective is to measure the effectiveness of education in supporting sustainable development and eradicating poverty. The study employed the co-integration method and the ARDL model to analyze the relationship between educational spending and economic growth. Data related to developmental and operational spending on education and the average oil and non-oil per capita income were examined. The results indicated a significant positive relationship between the average oil income per capita and developmental spending on education, reinforcing the hypothesis that education can contribute to sustainable development through investing oil revenues in education. The analysis further showed that any increase in oil income per capita leads to an increase in educational development spending. Regarding the second model, it was found that operational spending on education is associated with an increase in non-oil per capita income, supporting the hypothesis that education contributes to sustainable income and reduces dependence on oil. Additionally, the study revealed the challenge of the "diploma disease," where the focus on certificates rather than skill acquisition weakens Libya’s educational system. The study recommends allocating part of the oil revenues to improve the quality of education, integrating practical skills into curricula, and reforming the educational system to align with labor market needs.